(untitled) (Research, Society and Development, 2021)
Cancer patients were greatly affected by the covid-19 pandemic, because due to their poor health condition, these patients may be at high risk for developing more severe forms of covid-19 infection, due to the compromise of the immune system caused by the treatment. with chemotherapy and radiotherapy. The main objective of this study was to identify the main nursing care for cancer patients with covid-19 and, more specifically, describe the main health problems triggered by covid-19 and identify the health problems in cancer patients that can be enhanced by covid-19. This study is a descriptive research, with a search for articles carried out in digital libraries. The nursing team had to adapt to the new PPE routine to protect everyone, including the professionals themselves. There were significant changes in nursing care for cancer patients, which consisted mainly in the increase in the number of consultations via telemedicine and telephone, which reduced the number of patients in clinics and hospitals, as the nurse performed triage and directed the patients according to the clinical condition of each one. As for the care directed to cancer patients, according to the studies, all were maintained, with the difference that some were revised and adapted to meet the new demand imposed by the coronavirus.